Roxadustat Attenuates the Disruption of Epithelial Tight Junction in Caco2 Cells and a Rat Model of CKD Through MicroRNA-223 - Qu, Ning; Chen, Lei; Liang, Shanshan; Wei, Meng; Sun, Lingshuang; He, Quan; Xue, Jinhong; Wang, Meng; Shi, Kehui; Jiang, Hongli; Liu, Hua (Frontiers in Medicine, 2022)
Introduction Increasing evidence supports the idea that the disruption of epithelial tight junction proteins (TJPs) caused by accumulation of uremia toxins, such as homocysteine (Hcy), is one of the most important mechanisms underlying the damage of intestinal barrier function (IBF) in chronic kidney disease (CKD). Since the decrease of hypoxia inducible factor-1α (HIF-1α) is reported to be involved in Hcy-induced cell injury, and the upregulation of microRNA-223 (miR-223) plays a vital protective role in the impairment of IBF in the experimental colitis, we investigated the effect of HIF-1α stabilizer roxadustat on the disruption of TJPs induced by Hcy and CKD and the underlying mechanism. Methods Chronic kidney disease was induced in rats via 5/6 nephrectomy. In a series of experiments, the rats were treated orally with roxadustat of different doses. The expression of tight junction proteins, HIF-1α, and miR-223 was analyzed in different groups by western blotting analysis, RT-qPCR techniques and immunofluorescence. A series of experiments with cultured Caco2 cells was performed. Results The results showed that the expression of TJPs (occludin, claudin-1, and ZO-1) decreased significantly, accompanied by the reduction of HIF-1α and miR-223 in Hcy-treated Caco2 cells and colonic mucosa of uremic rats. The reduction of HIF-1α and miR-223 was reversed by roxadustat and the decrease of TJPs expression was attenuated in both Caco2 cells induced by Hcy and colon tissue of CKD rats. Furthermore, transfection with miR-223 mimics increased the expression of TJPs, while transfection with miR-223 inhibitor decreased their expression in Caco2 cells. MiR-223 inhibitor applied before roxadustat treatment partly diminished the effect of roxadustat on TJPs expression in Caco2 cells. Conclusion These results indicated that roxadustat attenuated the disruption of epithelial TJPs induced by Hcy in Caco2 cells and the damage of colonic epithelium in CKD rats through the upregulation of miR-223 induced by HIF-1α. A novel insight into the IBF dysfunction in CKD was provided, and it suggests a potential therapeutic use of roxadustat for the IBF dysfunction besides anemia in CKD.